PATTERN SYNTHESIS USING RANDOM ARRAY ELEMENT WEIGHTS - K. Ramya; G. S. N Raju; P. A. Sunny Dayal (Journal of Mechanics of Continua and Mathematical Sciences)
It is well known that methods of pattern synthesis reported in the open literature are mostly conventional. The methods include either standard distribution, empirical techniques, or analytical techniques. Every method has its own advantages and disadvantages regarding the overall pattern structure. The pattern structure is characterized by the main lobe and the side lobe behavior in the case of the sum pattern. On the other hand, difference patterns are the patterns characterized by the two different lobes and side lobe structures. Sequentially generating sum and difference patterns is advantageous in IFF radar applications. To simplify the design procedure and improve the pattern characteristics, an attempt is made to use random weights as amplitude excitation. Interestingly, useful results are obtained. The sum and difference are designed using the random approach and are presented in the sinθ domain for the arrays of dipoles and microstrip elements. The results are helpful for the array design depending on the applications and user requirements.